2015
DOI: 10.5606/kbbihtisas.2015.00008
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Tualang honey in reducing post-tonsillectomy pain

Abstract: Early postoperative pain was relieved slightly faster in Tualang honey + antibiotic group, which may be attributed to the soothing effect of honey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 17 publications
0
44
0
1
Order By: Relevance
“…Also, Abdullah et al, who studied the effect of honey on mitigating pain after tonsillectomy, pointed out that pain reduction in the honey group was higher than that in the control group. The main difference between this and the present study is that in the former, the participants received honey orally three times a day while honey was gargled by our subjects every six hours (13). Samdariya et al investigated the role of honey in lessening pain after radiation-induced mucositis in head and neck cancer patients and concluded that honey significantly decreased the severity of mucositis-associated pain and overall radiotherapy treatment duration.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Also, Abdullah et al, who studied the effect of honey on mitigating pain after tonsillectomy, pointed out that pain reduction in the honey group was higher than that in the control group. The main difference between this and the present study is that in the former, the participants received honey orally three times a day while honey was gargled by our subjects every six hours (13). Samdariya et al investigated the role of honey in lessening pain after radiation-induced mucositis in head and neck cancer patients and concluded that honey significantly decreased the severity of mucositis-associated pain and overall radiotherapy treatment duration.…”
Section: Discussionmentioning
confidence: 67%
“…Traditionally, honey has a substantial therapeutic and nutritional value, which is the key property of honey due to carbohydrates such as monosaccharide, fructose, and glucose. Honey accelerates and facilitates wound healing, and its antimicrobial and antiinflammatory properties reduce the ulcer pain, including throat ulcer caused by tonsillectomy/adenotonsillectomy (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antinociceptive property of honey is due to its ability to reduce plasma prostaglandins such as thromboxane B2, PGE2 and PGF2a [58,82] . The low water content and low pH (acidic) of honey due to the formation of gluconic acid results to an environment that is not favourable for bacteria to grow thus contributing to its antibacterial property [59] apart from having high viscosity that limits the solubility of oxygen and substances. Apart from that, the enzymatic glucose oxidation reaction also contributes to the antimicrobial property of honey alongside with phenolics and flavonoids [83,84] .…”
Section: G a L L E Y P R O O F Discussionmentioning
confidence: 99%
“…Manuka honey also shows antioxidant property as it attenuates H 2 O 2 -induced oxidative stress in human whole blood cell (Zivkovic et al 2018). Tualang honey, apart from having anticancer, antiinflammatory, antioxidant and wound healing properties, it also possess antinociceptive property in human and rats (Abdullah et al 2015;Aziz et al 2014). It was reported to improve cognitive function and memory performance (Al-Rahbi et al 2014;Othman et al 2011).…”
Section: Introductionmentioning
confidence: 99%